2010
DOI: 10.1016/j.tripleo.2009.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cone-beam CT parameters and sleep questionnaires in sleep apnea patients and control subjects

Abstract: Objective-To compare the Cone-Beam Computerized Tomography (CBCT) scan measurements between patients with Obstructive Sleep Apnea (OSA) and snorers to develop a prediction model for OSA based on CBCT imaging and the Berlin Questionnaire.Materials and methods-80 subjects (46 OSA patients with Apnea-Hypoapnea Index [AHI]≥ 10 and 34 snorers AHI<10 based on ambulatory somnographic assessment) were recruited through flyers and mail at USC School of Dentistry and at a private practice. Each patient answered the Berl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 29 publications
1
52
1
1
Order By: Relevance
“…20 Enciso et al conducted their study using the Newtom CBCT (Imageworks, New York, USA), which is the only commercially available CBCT that images the patient in supine position. 41 They were able to show that the OSA cases had a slightly more spherical airway shape than snorers that was consistent with Mayer et al's study, 26 a narrower LAT dimension of the airway compared with snorers that is consistent with Hora et al's study using MRI in awake patients. 42 A study by Pevernagie et al showed the effects of changes in body position on upper airway size and shape using 'fast' CT scan.…”
Section: Horizontal Versus Upright Cbctsupporting
confidence: 72%
“…20 Enciso et al conducted their study using the Newtom CBCT (Imageworks, New York, USA), which is the only commercially available CBCT that images the patient in supine position. 41 They were able to show that the OSA cases had a slightly more spherical airway shape than snorers that was consistent with Mayer et al's study, 26 a narrower LAT dimension of the airway compared with snorers that is consistent with Hora et al's study using MRI in awake patients. 42 A study by Pevernagie et al showed the effects of changes in body position on upper airway size and shape using 'fast' CT scan.…”
Section: Horizontal Versus Upright Cbctsupporting
confidence: 72%
“…Of all the studied parameters, only the ratio 'airway cross-section area/square area' showed statistically significant differences between both groups. Other studies compared the cross-sectional configuration of the oropharynx in OSA and non-OSA patients 53 and developed a prediction model for OSA based on CBCT features and sleep questionnaires 31 . Both studies 31,53 found a statistically significant smaller minimum cross-sectional area in OSA patients.…”
Section: Relationship Between Upper Airway and Obstructive Sleep Apnementioning
confidence: 99%
“…In occlusion 47,67 In maximum intercuspation 45,72,76 No 2 Not specified 3,24,29,31,37,44,[52][53][54]70 Not relevant 11,12,15,17,18,21,35,39,40,43,59,61,62,64,73,75 Tongue position control…”
Section: Yesmentioning
confidence: 99%
“…In the aetiology of OSA, some of the most important parameters are the airway volume, airway length and various anthropometric measurements [1,9,10,21,36]. According to the CT study performed by Enciso et al [10], men older than 57 years and individuals having narrow upper airway measurement have been identified as a high risk group for OSA.…”
Section: Discussionmentioning
confidence: 99%